Gorūṃ vīlāyata : Īṅgalāṇḍa, Skāṭalaṇḍa, Hāīlāṇḍasa, Pārīsa, Māraselasa, Mīlāna, Rīvīarā vageremāṃ jeyalā bāvaṭāonuṃ gaṇiū dāsatāna - Marajhabāna, Jahāṅgīra Beharāmajī (SAMP early 20th-century Indian books project, 1915)
Description of Europe.